blog/src/content/posts/2023-05-06-equivalences.lagda.md

179 lines
4.6 KiB
Markdown
Raw Normal View History

2023-08-31 03:47:22 +00:00
---
title: "Equivalences"
slug: "equivalences"
date: 2023-05-06
tags:
2023-08-31 08:07:03 +00:00
- type-theory
- agda
- hott
2023-08-31 03:47:22 +00:00
math: true
draft: true
---
<details>
<summary>Imports</summary>
```
{-# OPTIONS --cubical #-}
open import Agda.Primitive.Cubical
open import Cubical.Foundations.Equiv
open import Cubical.Foundations.Prelude
open import Data.Bool
```
</details>
```
Bool-id : Bool → Bool
Bool-id true = true
Bool-id false = false
unap : {A B : Type} {x y : A} (f : A → B) → f x ≡ f y → x ≡ y
unap p i = ?
-- Need to convert point-wise equality into universally quantified equality?
Bool-id-refl : (x : Bool) → (Bool-id x ≡ x)
Bool-id-refl true = refl
Bool-id-refl false = refl
```
The equivalence proof below involves the contractibility-of-fibers definition of
an equivalence. There are others, but the "default" one used by the Cubical
standard library uses this.
```
Bool-id-is-equiv : isEquiv Bool-id
```
In the contractibility-of-fibers proof, we must first establish our fibers. If
we had $(f : A \rightarrow B)$, then this is saying given any $(y : B)$, we must
provide:
- an $(x : A)$ that would have gotten mapped to $y$ (preimage), and
- a proof that $f\ x \equiv y$
These are the two elements of the pair given below. Since our function is `id`,
we can just give $y$ again, and use the `refl` function above for the equality
proof
```
```
The next step is to prove that it's contractible. Using the same derivation for
$y$ as above, this involves taking in another fiber $y_1$, and proving that it's
equivalent the fiber we've just defined above.
To prove fiber equality, we can just do point-wise equality over both the
preimage of $y$, and then the second-level equality of the proof of $f\ x \equiv
y$.
In the first case here, we need to provide something that equals our $x$ above
when $i = i0$, and something that equals the fiber $y_1$'s preimage $x_1$ when
$i = i1$, aka $y \equiv proj_1\ y_1$.
```
-- 2023-05-13: Favonia's hint is to compute "ap g p", and then concatenate
-- it with a proof that g is the left-inverse of f
-- ok i'm pretty sure this should be the g = f^-1
Bool-id-inv : Bool → Bool
Bool-id-inv b = (((Bool-id-is-equiv .equiv-proof) b) .fst) .fst
Bool-id-inv-is-inv : (b : Bool) → Bool-id-inv (Bool-id b) ≡ b
Bool-id-inv-is-inv true =
Bool-id-inv (Bool-id true)
≡⟨ refl ⟩
Bool-id-inv true
≡⟨ refl ⟩
-- This isn't trivially true?
(Bool-id-is-equiv .equiv-proof true .fst) .fst
≡⟨ ? ⟩
true
Bool-id-inv-is-inv false = ?
Bool-id-is-equiv .equiv-proof y .fst = y , Bool-id-refl y
Bool-id-is-equiv .equiv-proof y .snd y₁ i .fst =
let
eqv = snd y₁
-- eqv : Bool-id (fst y₁) ≡ y
-- this is the second pieece of the other fiber passed in
eqv2 = eqv ∙ sym (Bool-id-refl y)
-- eqv2 : Bool-id (fst y₁) ≡ Bool-id y
-- concat the fiber (Bool-id (fst y₁) ≡ y) with (y ≡ Bool-id y) to get the
-- path from (Bool-id (fst y₁) ≡ Bool-id y)
-- Ok, unap doesn't actually exist unless f is known to have an inverse.
-- Fortunately, because we're proving an equivalence, we know that f has an
-- inverse, in particular going from y to x, which in this case is also y.
eqv3 = unap Bool-id eqv2
-- Then, ap g p should be like:
ap-g-p : Bool-id-inv (Bool-id (fst y₁)) ≡ Bool-id-inv (Bool-id y)
ap-g-p = cong Bool-id-inv eqv2
-- OHHHHH now we just need to find that Bool-id-inv (Bool-id y) ≡ y, and
-- then we can apply it to both sides to simplify
-- So something like this:
-- left-id : Bool-id-inv ∙ Bool-id ≡ ?
-- left-id = ?
eqv3 = cong Bool-id-inv eqv2
give-me-info = ?
-- eqv3 : fst y₁ ≡ y
-- Use the equational reasoning shitter
final : y ≡ fst y₁
final =
y
≡⟨ ? ⟩
fst y₁
```
Blocked on this issue: https://git.mzhang.io/school/cubical/issues/1
```
eqv4 = ?
eqv4 = sym eqv3
-- eqv4 : y ≡ fst y₁
in
eqv4 i
```
Now we can prove that the path is the same
\begin{CD}
2023-08-31 08:07:03 +00:00
A @> > > B \\\
@VVV @VVV \\\
C @> > > D
2023-08-31 03:47:22 +00:00
\end{CD}
- $A \rightarrow B$ is the path of the original fiber that we've specified, which is $f\ x \equiv y$
- $C \rightarrow D$ is the path of the other fiber that we're proving, which is $proj_2\ y_1$
So what we want now is `a-b ≡ c-d`
```
Bool-id-is-equiv .equiv-proof y .snd y₁ i .snd j =
let
a-b = Bool-id-refl y
c-d = y₁ .snd
in
?
2023-08-31 08:07:03 +00:00
```
2023-08-31 03:47:22 +00:00
Blocked on this issue: https://git.mzhang.io/school/cubical/issues/2
2023-08-31 08:07:03 +00:00
```
2023-08-31 03:47:22 +00:00
```
## Other Equivalences
There are 2 other ways we can define equivalences:
TODO: Talk about them being equivalent to each other